Corruption and Dispossession in Middlesex - Mulmi, Saroj Man (Cognition, 2019)
Jeffrey Eugenides’s Middlesex is a story of Greek migrants who find refuge in America after their dispossession and displacement. The dislocation is compounded by moral corruption of the characters associated with breakdown of familial and social values along with the new found liberty they enjoyed in the new land unleashing specter of recessive mutation giving birth to family problem. The study traces the root of corruption by analyzing the text to establish events that take place in remote space and time can have far reaching consequences affecting the present life.